The Ability Of Mathematical Representation On Junior High School Students In Rectangular And Triangle Based On Gender - Azizah, Annisa Nur; Kusmayadi, Tri Atmojo; Fitriana, Laila; Nataliliana, Claireza; Hermansyah, Beny (Lppm Universitas Nurul Hud, 2024)
The ability of representation mathematical is an ability to express or model the mathematical idea into other forms such as words, pictures, and symbols. A study on the ability of mathematics representation is required for the students; therefore, they can express their idea easily by interpreting their thought relating to mathematics problems. This research is a descriptive qualitative method which aimed to find out the description of student' ability of the mathematical representation on rectangular and triangle based on gender. The subjects of this research are 26 students of eight grades consisted of 11 female students and 15 male students. The technique of collecting data was done by using the test method and interview. The test instrument used is 6 essay tests. The data analysis technique is by analyzing the results of the test data. The research result showed that students' mathematical representation ability are categorized well enough. From the results of the data obtained, it can be concluded that the ability of mathematical representation for male students is evenly distributed because there are results for each category. As for the female students, the average has a high mathematical representation ability